Pemberdayaan Masyarakat dalam Pengolahan Limbah Dapur Menjadi Pupuk Organik Cair Berbasis Rumah Tangga - Wiwin Yuliani; Novia Indah Lestari; Bayu Mahendra; Putri Wening Ratrinia; Lisa Astria Milasari (Abdibaraya, 2026)
The accumulation of household organic waste in residential areas of Tasikmalaya has become an environmental problem due to inadequate waste management at the source level. This condition increases the burden on landfills and poses potential risks of environmental pollution. This community service program aims to enhance community capacity in processing kitchen waste into liquid organic fertilizer (LOF) at the household level using simple, low-cost, and applicable methods. The implementation method includes situation analysis, socialization of the economic value of waste, technical training on LOF production, and assistance during the fermentation process using EM4 bioactivator. The program involved 30 participants, consisting of housewives and environmental cadres. Evaluation was conducted by measuring participants’ knowledge and skills before and after the activity. The results indicate a significant improvement, with participants’ knowledge increasing from 35% to 95%, technical skills from 10% to 85%, and awareness of the economic value of waste from 20% to 90%. The community can now produce LOF independently to support small-scale urban farming in limited land areas. In addition, the utilization of kitchen waste contributes to reducing the volume of waste disposed to landfills. The resulting product can be used as an economical and environmentally friendly alternative fertilizer and has the potential to be developed into a value-added product. Therefore, community empowerment through kitchen waste management is proven effective in promoting household-level food self-sufficiency, increasing environmental awareness, and supporting sustainable waste management practices